Images of women in the media : report on existing research in the European Union. (Employment and social affairs, 1999)
Abstract: This report provides an analytical overview of research into gender portrayal in the media of the EU member states, and, where relevant, media in other countries such as Norway, Iceland and several countries in Central Europe. The report is based on five studies each of which covers a number of different countries, and a study of gender and new media.